EVALUASI PROGRAM PENINGKATAN KOMPETENSI GURU MADRASAH IBDTIDAIYAH PADA DIKLAT PENYUSUNAN RPP DI BALAI DIKLAT KEAGAMAAN MEDAN - Safaruddin Safaruddin; Candra Wijaya; Rahmadi Ali (Edukasi Islami : Jurnal Pendidikan Islam, 2020)
This research was conducted at the Balai Diklat Keagamaan Medan with the aim of evaluating the Madrasah teacher competency improvement program in substantive technical training for the preparation of the RPP for Madrasah Ibtidaiyah Teachers. This type of research is qualitative research using the CIPP (context, input, process and product) evaluation model which focuses on core questions, namely the context of the Madrasah teacher competency improvement program, the input conditions for the Madrasah teacher competency improvement program, the process conditions for the improvement program. Madrasah teacher competencies and product conditions in the Madrasah teacher competency improvement program.The results of this study consisted of 4 components. First. The context dimension is the analysis of the legal basis criteria, that every education and training must have a legal umbrella including Regulation of the Minister of Religion 10 of 2018 concerning amendments to PMA No. 59 of 2015 concerning the Organization and Work Procedure of the Education and Training Center and the Criteria for the Analysis of the Education and Training Organization, that the education and training organization that manages the education and training activities has a legal basis and also has a legal basis at work, the education and training organization is a transition of responsibility from the Kasi to the training committee. Educational and Religious Technical Staff were then given a Letter of Appointment (SK).Second. The input dimension is the availability of reliable resources such as lecturers / teaching staff, the availability of adequate facilities and infrastructure for training participants, the availability of state-borne funding. Third. The process dimension, namely the implementation of the training program as planned, the widyaswara / teaching staff master the training material presented, the lecturers master the learning method in delivering the material, the lecturers use learning media in presenting the material, the training participants create study groups, practical training participants make RPP. Fourth. Product dimensions.  namely teachers do not understand core competencies and basic competencies in lesson plans, teachers can formulate indicators, teachers are able to formulate learning objectives, teachers can determine learning methods, teachers can arrange learning activities, teachers can formulate learning resources and media, teachers can formulate assessments in learning.